Synchrotron-based P K-edge XANES spectroscopy reveals rapid changes of phosphorus speciation in the topsoil of two glacier foreland chronosequences - Prietzel, Jörg; Dümig, Alexander; Wu, Yanhong; Zhou, Jun; Klysubun, Wantana (Geochimica et cosmochimica acta, 2013)
Phosphorus (P) is a crucial element for life on Earth, and the bioavailability of P in terrestrial ecosystems, which is dependent on the soil P stock and its speciation, may limit ecosystem productivity and succession. In our study, for the first time a direct speciation of soil P in two glacier foreland chronosequences has been conducted using synchrotron-based X-ray Absorption Near-Edge Structure (XANES) spectroscopy. The chronosequences are located in the forefields of Hailuogou Glacier (Gongga Shan, China) and Damma Glacier (Swiss Alps). The age since deglaciation of the investigated soils ranges from 0 to 120years at Hailuogou, and from 15 to >700years at Damma. Differences in climate conditions (cooler at Damma, in contrast to Hailuogou precluding the establishment of forest in advanced ecosystem succession stages) and in the chemical composition of the parent material result in different soil contents of total P and Fe/Al oxyhydroxides, which are much smaller at Damma than at Hailuogou. Nevertheless, both chronosequences show similar trends of their topsoil P status with increasing soil age. Our study reveals a rapid change of topsoil P speciation in glacier retreat areas already during initial stages of pedogenesis: Initially dominating bedrock-derived apatite-P and Al-bound P is depleted; Fe-bound P and particularly organically-bound P is accumulated. Organic P strongly dominates in the topsoil of the mature soils outside the proglacial area of Damma Glacier (age 700–3000years), and already 50years after deglacation in the topsoil of the retreat area of Hailuogou Glacier. A key factor for the change in topsoil P speciation is the establishment of vegetation, resulting in soil organic matter (SOM) accumulation as well as accelerated soil acidification and apatite dissolution by organic acids, which are produced by SOM-degrading micro-organisms, mykorrhiza fungi, and plant roots. Particularly the succession of grassland to forest seems to accelerate the transformation of topsoil P from apatite-P into organic P. The conceptual model developed by Walker and Syers (1976) to explain long-term (millennial) changes of P speciation, availability, and turnover in soils and terrestrial ecosystems seems to be valid to describe short-term changes of P speciation and P availability in proglacial topsoils already within a century of initial soil formation. Because the apatite-depleted topsoil horizons in the young proglacial soils are shallow, the change of topsoil P speciation should not seriously affect P availability and the P acquisition strategy of adult trees, whose roots can easily access apatite-containing C horizons. In contrast, P acquisition strategies of fungi, micro-organisms and plants confined to the topsoil probably change from apatite dissolution to mineralization of organic P already within <3000years in a proglacial ecosystem succession from bare soil to grassland (Damma Glacier Chronosequence) or even within <100years in a proglacial ecosystem succession to forest (Hailuogou Glacier Chronosequence).